Ex Vivo Expanded Human Non-Cytotoxic CD8+CD45RClow/− Tregs Efficiently Delay Skin Graft Rejection and GVHD in Humanized Mice - Bézie, Séverine; Meistermann, Dimitri; Boucault, Laetitia; Kilens, Stéphanie; Zoppi, Johanna; Autrusseau, Elodie; Donnart, Audrey; Nerrière-Daguin, Véronique; Bellier-Waast, Frédérique; Charpentier, Eric; Duteille, Franck; David, Laurent; et al. (Frontiers in Immunology, 2018)
Both CD4+ and CD8+ Tregs play a critical role in the control of immune responses and immune tolerance; however our understanding of CD8+ Tregs is limited while they are particularly promising for therapeutic application. We report here existence of highly suppressive human CD8+CD45RClow/- Tregs expressing Foxp3 and producing IFNg, IL-10, IL-34 and TGFb to mediate their suppressive activity. We demonstrate that total CD8+CD45RClow/- Tregs can be efficiently expanded in presence of anti-CD3/28 mAbs, high dose IL-2 and IL-15 and that such expanded Tregs efficiently delay GVHD and human skin transplantation rejection in immune humanized mice. Robustly expanded CD8+ Tregs displayed a specific gene signature, upregulated cytokines and expansion in presence of rapamycin greatly improved proliferation and suppression. We show that CD8+CD45RClow/- Tregs are equivalent to canonical CD4+CD25highCD127low/- Tregs for suppression of allogeneic immune responses in vitro. Altogether, our results open new perspectives to tolerogenic strategies in human solid organ transplantation and GVHD.